The Epidemiology of Diabetic Kidney Disease - Ellen K. Hoogeveen (Kidney and Dialysis, 2022)
Globally, the incidence and prevalence of diabetes mellitus has risen dramatically, owing mainly to the increase in type 2 diabetes mellitus (T2DM). In 2021, 537 million people worldwide (11% of the global population) had diabetes, and this number is expected to increase to 783 million (12%) by 2045. The growing burden of T2DM is secondary to the pandemic of obesity, which in turn has been attributed to increased intake of processed food, reduced physical activity, and increased sedentary behaviour. This so-called western lifestyle is related with the global increase in urbanization and technological development. One of the most frequent and severe long-term complications of diabetes is diabetic kidney disease (DKD), defined as chronic kidney disease in a person with diabetes. Approximately 20–50% of patients with T2DM will ultimately develop DKD. Worldwide, DKD is the leading cause of chronic kidney disease and end-stage kidney disease, accounting for 50% of cases. In addition, DKD results in high cardiovascular morbidity and mortality, and decreases patients’ health-related quality of life. In this review we provide an update of the diagnosis, epidemiology, and causes of DKD.